An Exploratory Study Of Mental Health Among Creative Media Workers - Dini Farhana Baharudin; Melati Sumari; Yusni Mohamad Yusop; Zaida Nor Zainudin (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
Volume :15 (SUPP1)